2021
DOI: 10.1039/d1ay01602d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of falsified clopidogrel in the presence of excipients using voltammetry

Abstract: There has been a recent surge in the amount of substandard and falsified clopidogrel. Pharmacopeial based assays using high performance liquid chromatograph and mass spectroscopy are widely used for measurement...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…These results indicate that measurements of melatonin tablets can be conducted in the presence of the excipients and thus reduce the need for extra sample preparation steps allowing for total analysis. Our findings are identical to other studies which have shown that electrochemical measurements can be conducted in particulate solutions [38][39][40]. Given our ability to clearly detect the presence of melatonin within the tablet without additional sample preparation steps, we conducted a calibration response in the presence of excipients.…”
Section: Analytical Performance Of the 3d-printed Pestle And Mortar F...supporting
confidence: 82%
See 1 more Smart Citation
“…These results indicate that measurements of melatonin tablets can be conducted in the presence of the excipients and thus reduce the need for extra sample preparation steps allowing for total analysis. Our findings are identical to other studies which have shown that electrochemical measurements can be conducted in particulate solutions [38][39][40]. Given our ability to clearly detect the presence of melatonin within the tablet without additional sample preparation steps, we conducted a calibration response in the presence of excipients.…”
Section: Analytical Performance Of the 3d-printed Pestle And Mortar F...supporting
confidence: 82%
“…Calibrations were conducted in the concentration range of 300 to 37.5 µg/mL. This approach was taken as we have previously shown that tablet excipients can reduce the current response of melatonin and other pharmaceutical active ingredients [38][39][40]. To evaluate the stability for repeated measurements of melatonin tablets, five repeated measurements were conducted using melatonin tablets.…”
Section: Electrochemical Measurements Using the Pestle And Mortarmentioning
confidence: 99%
“…There are several methods reported in the literature for the analysis of clopidogrel bisulfate 5 , such as UV/Vis spectrophotometry, high-performance liquid chromatography (HPLC), micellar liquid chromatography (MLC), micellar electrokinetic chromatography (MEKC), high-performance thin layer chromatography (HPTLC), and liquid chromatography-tandem mass spectrometry (LC-MS/MS) 6 . Also, electrochemical methods were used for the analysis of clopidogrel bisulfate [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%